537 Oversensing due to micro-air bubbles leading to inappropriate shocks in patient with subcutaneous implantable cardioverter defibrillator. (8th December 2021) - Seganfreddo, Francesca; Golino, Michele; Ceriani, Francesca; Matteo, Federica; Morello, Matteo; Licciardello, Claudio; Marazzato, Jacopo; Vilotta, Manola; Caravati, Fabrizio; De Ponti, Roberto
Abstract: Aims: Subcutaneous air has been reported as uncommon cause of early device malfunction after implantation of subcutaneous implantable cardioverter defibrillator (S-ICD). Methods and results: A 43-year-old man was admitted to our hospital due to syncopal episodes. During a brain computed tomography (CT), he was resuscitated from cardiac arrest due to ventricular fibrillation. Further investigations excluded ischaemic heart disease and cardiac magnetic resonance showed signs of prior myocarditis. After successful screening, an S-ICD was inserted for secondary prevention using the standard technique. The chest X-ray excluded acute post-procedural complications. Three days after implantation, he experienced two inappropriate shocks while conscious. Device interrogation revealed frequent high-amplitude signals followed by two shocks (Figure 1A and B) that could be interpreted as oversensing. During provocative maneuvers on the generator case, minimal and intermittent noise only on the secondary sensing vector was observed. Lateral and antero-posterior chest X-ray excluded subcutaneous air. However, the general agreement based on previous reports was that oversensing as observed in Figures 1A and B was typical for noise due to micro-air bubbles in the connection between the lead and the generator case. As a consequence, the sensing vector was successfully changed and no other inappropriate shocks were observed during follow-up. Conclusions: Entrapped micro-air bubbles in the connection between the leads and the generator case can cause inappropriate shocks in the early period after S-ICD implantation. Timely recognition of this complication is important to prevent inappropriate shocks. It can occur shortly after the procedure even if the intra-procedural parameters were normal and chest X-ray excluded acute complications. As demonstrated in our case, the device can be reprogrammed using another sensing vector to solve these oversensing problems.